Effect of walking exercise combined with slow deep breathing on blood pressure among hypertensive pregnant women - Okke Afivah Murti; Cucuk Kunang Sari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Hypertension in pregnancy is one of the complications that contributes to the high maternal mortality rate. Non-pharmacological management such as walking exercise and slow deep breathing can be alternative methods to reduce blood pressure. However, research on the combination of these interventions is still limited. Purpose: To determine the effect of walking exercise combined with slow deep breathing on blood pressure in pregnant women with hypertension. Method: This study used a quantitative design with a quasi-experimental approach using a one-group pretest-posttest design. The sample was selected using total sampling technique with 30 respondents. The intervention, consisting of walking exercise combined with slow deep breathing, was conducted for 10 minutes, 3 times a week. The instruments used were a respondent characteristic questionnaire and an obsetvation sheet for blood pressure measurements. Results: After being given walking exercise combined with slow deep breathing, the average systolic blood pressure decreased to 127.00 mmHg and diastolic pressure decreased to 80.63 mmHg. The Effect of Walking Exercise and Slow Deep Breathing on Blood Pressure in Pregnant Women with Hypertension. The results of the Paired t-test showed a p-value of 0.000 (p<0.05). Conclusion: The results showed that there is a significant effect of Walking exercise combined with slow deep breathing on blood pressure in pregnant women with hypertension.